Buku alumni Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga Yogyakarta tahun 1977 - 1997 - UNIVERSITAS_ISLAM_NEGERI_SUNAN_KALIJAGA (Fak. Dakwah dan Komunikasi UIN Sunan Kalijaga, 2014)
khus, 1/ws.c.1